Creative soccer training - Seeger, F.; Favé, L. (Meyer & Meyer Sport (UK) Ltd., 2017)
Creative Soccer Training is the sequel to the top-selling book, The Soccer Games and Drills Compendium. The authors have extended their realistic training approach to present 350 new and innovative training exercises. With its tried and tested format, Creative Soccer Training continues and enhances the practice-oriented methods outlined in the Games and Drills Compendium, but in this book the methods are developed for more ambitious and advanced players. The creative training areas are divided into: